PENGARUH GAYA SUPERVISI, KOMPETENSI TERHADAP KINERJA KEPALA DESA DI LINGKUNGAN PEMERINTAHAN KOTA SUNGAI PENUH - Mukhlis Yunus; Afrinovera (Pendidikan Matematika | STKIP YM Bangko, 2020)
This study aims to determine (1) the effect of supervision on the performance of heads in Village the Sungai Penuh City government environment (2) the influence of competence on performance government environment in the Sungai Penuh City. This research was carried out by using an explanatory method (Survey explanatory confirmatory) and using data analysis techniques path analysiswith the approach of Structural Equation Modeling (SEM) Partial Least Square (PLS). The results showed that there was no significant effect between supervision of the performance of the village head and there was a significant influence between competencies on the performance of the village head of the Sungai Penuh City administration.